Reducing Cognitive Load in 3D Geometry with Culturally Responsive Augmented Reality Scaffolds - Mega Obukohwo OYOVWE; Sylvia Onataghogho OYOVWE (SJME (Supremum Journal of Mathematics Education), 2026)
Mathematical problem solving places heavy demands on students' working memory capacity, particularly when they learn abstract geometric concepts such as three-dimensional curved shapes. Rather than reporting empirical findings, this theoretical synthesis examines the intersection of cognitive load theory, culturally responsive digital scaffolding, and technology-enhanced mathematics learning. Drawing on empirical evidence from cognitive science and mathematics education, we synthesize previous findings and distinguish them from the theoretical propositions developed in this paper. We propose a framework for designing culturally responsive digital scaffolds that reduce extraneous cognitive load while freeing working memory resources for deeper conceptual engagement. The paper synthesizes findings from three interconnected research strands: (1) cognitive load theory and its applications in digital learning environments, (2) culturally responsive mathematics education and ethnomathematics as cognitive scaffolds, and (3) augmented reality (AR) as a tool for reducing cognitive load in spatial reasoning tasks. We argue that culturally familiar contexts reduce the need for effortful translation of abstract symbols, thereby freeing cognitive resources for problem-solving. Furthermore, AR-enabled visualizations externalize abstract mathematical structures, minimize extraneous processing, and facilitate germane cognitive engagement. The proposed Techno-Ethno-Realistic Mathematics Education (TE-RME) framework, which synthesizes digital tools, cultural and ethnomathematical contexts, and realistic problem-solving, integrates these insights to support inclusive, equitable, and meaningful mathematics learning.